Hubungan Kepatuhan SPO Rawat Luka, Penerapan Bundles Surgical Site Infection, dan Faktor Pasien dengan Kejadian Ido Pada Pasien Sectio Ceasarea - Slamet Djoko Sunarko; Yuly Peristiowati; Joko Prasetyo (Universitas Katolik Widya Karya Malang, 2023)
Introduction: Health Care Associated Infections (HAIs) often occur in hospitals. Infections classified as HAIs are surgical site infections. Compliance with wound care according to SPO, application of SSI budles and SC patient factors, namely: age, blood sugar levels and albumin levels contribute to the incidence of surgical site infections. This study aims to explain the relationship between SPO adherence to wound care, application of bundles surgical site infection, and patient factors with the incidence of SSI in sectio caesarea patients. Methods: This study uses a literature review. Search strategy on ProQuest, Google Scholar, PubMed. The journal reviewed is research on the relationship between SPO compliance with wound care, application of bundles surgical site infection, and patient factors with the incidence of SSI in cesarean section patients published in 2016-2023. Journals that did not meet the inclusion criteria were excluded, so that 5 journals were reviewed. Results: there is a relationship between adherence to SPO wound care, application of bundles surgical site infection, age, blood sugar levels, and albumin levels of SC patients to the incidence of SSI. Discussion: Research recommends that nurses adhere to SPO and implement SSI bundles strictly in a compliant manner, as well as monitoring patient factors, such as: age, blood sugar levels, patient albumin levels are very important in preventing infection in the operating area.